2021
DOI: 10.4081/ijfs.2021.9988
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of alkaline electrolyzed water in reducing bacterial load on surfaces intended to come into contact with food

Abstract: Alkaline electrolyzed water (REW) is known for its cleaning action. The aim of this work was to assess REW effectiveness in reducing microbial load on surfaces intended for contact with food. Stainlesssteel surfaces were experimentally contaminated, bacterial inactivation was tested before and after treatment with REW. Treatment with REW was operated spraying it on the contaminated plates until drying. Tests were conducted for Salmonella spp., Listeria spp., Staphylococcus aureus and Escherichia coli. The trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…NaOH ions and hydrogen gas were formed at the cathode (Table 1). AlEW with comparable alkalinity qualities (>pH 7.0) would have the same efficacy as NaOH and perform well in the alkaline wash as a potential green degreaser for meat processing stainless steel surfaces (Tomasello et al, 2021; Wang et al, 2016).…”
Section: Overview Of Alewmentioning
confidence: 99%
See 1 more Smart Citation
“…NaOH ions and hydrogen gas were formed at the cathode (Table 1). AlEW with comparable alkalinity qualities (>pH 7.0) would have the same efficacy as NaOH and perform well in the alkaline wash as a potential green degreaser for meat processing stainless steel surfaces (Tomasello et al, 2021; Wang et al, 2016).…”
Section: Overview Of Alewmentioning
confidence: 99%
“…The meat processing environment requires cost–effective and efficient cleaning to maintain cleanliness at the lowest possible cost (Khalid et al, 2019). This review proposed alkaline electrolyzed water (AlEW) as a potential green degreaser for meat processing stainless steel surfaces instead of traditional alkaline wash such as NaOH in a cleaning program (Tomasello et al, 2021; Wang et al, 2016). The process of generating AlEW involves passing an electric current through a small amount of NaCl dissolved in water to increase the pH alkalinity, producing a combination of hypochlorous acid and sodium hydroxide (Khalid, Sulaiman, Ab Aziz, et al, 2020; Veasey & Muriana, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the alkaline ionised water (AIW) showed excellent bactericidal effects in inactivating food-borne pathogens, such as Salmonella, Listeria monocytogenes, Vibrio parahaemolyticus and Escherichia coli (Tomasello et al, 2021). Additionally, AIW has been applied to inactivate the surface pathogenic bacteria in fresh fruits, ready-to-eat salads and the environment (Tomasello et al, 2021;Bajgai et al, 2022). Lin et al (2020) claimed that AIW positively affected the water retention capacity, colour, texture and lipid oxidation of catfish fillets compared to acidic electrolyzed water.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, instead of an all-in/all-out loading system, chambers were filled with continuous additions of pieces of meat. Animals and humans are usually the major sources of bacterial food contamination in the meat industry, but products are often contaminated through contact with equipment surfaces, such as shredders, slicers, and cutting boards (Tomasello et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%